A Markov regenerative process model for phased mission systems under internal degradation and external shocks. (November 2021) - Li, Xiang-Yu; Huang, Hong-Zhong; Li, Yan-Feng; Xiong, Xiaoyan
Highlights: A Markov regenerative process model is developed to model the PMS under mixed random shocks. A Monte Carlo simulation procedure is given to validate the proposed method. The altitude and orbit control system is used to illustrate the proposed method. The result analysis shows the influence of different shocks parameters. Abstract: Recently, phased mission systems (PMSs) have been widely studied due to their wide range of applications, such as man-made satellites or spacecraft. The lifetime of the PMSs can be separated into several phases, in which their tasks, system configurations, and failure criteria could be different. Meanwhile, the randomly occurred shocks, such as the space radiation from outer space, will cause additional wear and fatal damage on the electronic devices in these systems, which will obviously affect the system reliability. To consider these shocks' effect in the reliability modeling of the PMSs, a Markov regenerative process (MRGP) based model is proposed in this paper. Firstly, shock models for components and the basic conceptions of MRGP are introduced. Then, a simple cold standby system is used to show the proposed MRGP model for systems under mixed shocks. And a Monte Carlo simulation procedure is applied to verify the results. At last, by integrating the proposed MRGP model and the modular method for PMSs, the reliability of an AOCS in a spacecraft is assessed to show the proposed method.